Comparative analysis of lincRNA in insect species - Alberto Lopez-Ezquerra; Mark C. Harrison; Erich Bornberg-Bauer (BMC Evolutionary Biology, 2017)
Abstract Background The ever increasing availability of genomes makes it possible to investigate and compare not only the genomic complements of genes and proteins, but also of RNAs. One class of RNAs, the long noncoding RNAs (lncRNAs) and, in particular, their subclass of long intergenic noncoding RNAs (lincRNAs) have recently gained much attention because of their roles in regulation of important biological processes such as immune response or cell differentiation and as possible evolutionary precursors for protein coding genes. lincRNAs seem to be poorly conserved at the sequence level but at least some lincRNAs have conserved structural elements and syntenic genomic positions. Previous studies showed that transposable elements are a main contribution to the evolution of lincRNAs in mammals. In contrast, plant lincRNA emergence and evolution has been linked with local duplication events. However, little is known about their evolutionary dynamics in general and in insect genomes in particular. Results Here we compared lincRNAs between seven insect genomes and investigated possible evolutionary changes and functional roles. We find very low sequence conservation between different species and that similarities within a species are mostly due to their association with transposable elements (TE) and simple repeats. Furthermore, we find that TEs are less frequent in lincRNA exons than in their introns, indicating that TEs may have been removed by selection. When we analysed the predicted thermodynamic stabilities of lincRNAs we found that they are more stable than their randomized controls which might indicate some selection pressure to maintain certain structural elements. We list several of the most stable lincRNAs which could serve as prime candidates for future functional studies. We also discuss the possibility of de novo protein coding genes emerging from lincRNAs. This is because lincRNAs with high GC content and potentially with longer open reading frames (ORF) are candidate loci where de novo gene emergence might occur. Conclusion The processes responsible for the emergence and diversification of lincRNAs in insects remain unclear. Both duplication and transposable elements may be important for the creation of new lincRNAs in insects.